Comparison of Standard Caribbean Coral Reef Monitoring Protocols and Underwater Digital Photogrammetry to Characterize Hard Coral Species Composition, Abundance and Cover - Barrera-Falcon, Erick; Rioja-Nieto, Rodolfo; Hernández-Landa, Roberto C.; Torres-Irineo, Edgar (Frontiers in Marine Science, 2021)
The precise assessing and monitoring of coral reefs are necessary to address and understand the threats and changes in coral communities. With the development of new technologies and algorithms for image processing, new protocols like underwater photogrammetry are implemented to study these ecosystems. This study compares the main ecological metrics for reef condition assessment, obtained with an underwater digital photogrammetry protocol (UWP) and traditional sampling design simulations in coral reefs of the Cozumel Reefs National Park. Three orthomosaics (380 m2) per reef on six fringing reefs were constructed, and the hard coral community characterized using a Geographic Information System (GIS). The orthomosaics were also used as a basis to simulate transect lines and obtain data on the hard coral community according to the video transect (VT) protocol, point intercept (PIT) protocol, and the Atlantic and Gulf Rapid Reef Assessment (AGRRA) protocol. Higher colony abundance, species richness, and lower coral cover estimates (p < 0.05) were obtained with the UWP. This protocol was also sensitive to small sized species. All the sampling designs showed similar capability to identify dominant species in terms of colony abundance and coral cover. The VT, PIT, and AGGRA showed similar coral cover values (p > 0.05), which seems to indicate that these sampling designs overestimate this important metric. Our results will help to understand and integrate the observations obtained with UWP with long-term data obtained with commonly used monitoring protocols in the Caribbean region.